PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH DALAM PEMBEBASAN TANAH UNTUK KEPENTINGAN UMUM - LALU MUHAMAMAD FAISAL; admin admin (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2019)
This research aimed at describing the juridical based (essentially) to the protection of law theland right owner; juridical requirements of classification of land right as the basis of arising theland right; and factors affect the upaya protection of law to the owner of land right. This researchimplemented the descriptive analytic method to viewed from normative aspects. The datashowed that the society has less comprehension on the function of land certificate as the letterof land right since they do not get sufficient socialization on it. Concerning law and the JudgesAgreement of MA not clear stated based on the principles, bases, and theoretical law on land,but strongly based on proofing the right of land only (certificate). Because of that the protectionof law to the owner of land right was not yet get the protection of law, though based on verse 60Agrarian State Minister Act Number 3 Year 1997 about law on the implementation ofGovernment Act Number 24 Year 1997 (f) states that the registration of land used someprevious requirements to get the land right are petuk Pajak Bumi/Landrente, girik, pipil, kekitirdan Verponding Indonesia before the Government Act Number 10 Year 1961 must beconcerned in front of the court.